2007
DOI: 10.1158/1541-7786.mcr-06-0069
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Bladder Tumor CellsIn vivoand in the Urine with a Peptide Identified by Phage Display

Abstract: Bladder cancer is one of the most common tumors of the genitourinary tract. Here, we use phage display to identify a peptide that targets bladder tumor cells. A phage library containing random peptides was screened for binding to cells from human bladder tumor xenografts. Phage clones were further selected for binding to a bladder tumor cell line in culture. Six clones displaying the consensus sequence CXNXDXR X

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 29 publications
0
87
0
Order By: Relevance
“…This result was demonstrated in previous free peptide studies, showing that CSNRDARRC has high affinity for human bladder tumors. 30,35 We previously reported the high affinity of this peptide to various bladder cancer cells, including human, murine, and canine cells 36 ( Figure 8A and B). Here, we incubated the pMCNPs with canine bladder cancer cells (K9TCC).…”
Section: Intracellular Uptake Of Pmcnps By K9tcc Bladder Cancer Cellsmentioning
confidence: 81%
See 1 more Smart Citation
“…This result was demonstrated in previous free peptide studies, showing that CSNRDARRC has high affinity for human bladder tumors. 30,35 We previously reported the high affinity of this peptide to various bladder cancer cells, including human, murine, and canine cells 36 ( Figure 8A and B). Here, we incubated the pMCNPs with canine bladder cancer cells (K9TCC).…”
Section: Intracellular Uptake Of Pmcnps By K9tcc Bladder Cancer Cellsmentioning
confidence: 81%
“…11,30 The biodistribution and tumor accumulation of the modified nanoparticles in each step were compared in parallel through in vivo systems. We demonstrated that adding new components, such as new MR contrast agents or targeting ligands, clearly changed its in vivo biodistribution by altering their physicochemical properties of the particles.…”
mentioning
confidence: 99%
“…There are many advantages to the use of small peptides including low cost, absence of significant immunogenicity, and ease of coupling to cytotoxic agents. The most important advantage of peptides is their versatility (Aggarwal et al, 2006;Jäger et al, 2007;Lee et al, 2007;Rasmussen et al, 2002). For example, tumor binding peptide sequences can be incorporated into the coat proteins of viruses (Grifman et al, 2001;White et al, 2004), and novel targeting tools, such as liposomes and nanoparticles, can be used together with the peptides (Hajitou et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RNA aptamers have been developed for use as targeting and imaging tools (Hicke et al, 2001;. However, to expand the potential utility of TNC as a tumor microenvironment target, a versatile alternative molecule such as a small peptide should also be developed (Aggarwal et al, 2006;Jäger et al, 2007;Lee et al, 2007;Rasmussen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A Bld-1 peptide of CSNRDARRC, which binds to bladder tumor cell, has been identified by phage display [102]. Jung et al combined the tumor targeting peptide Bld-1 with a pro-apoptosis D (KLA) 2 and formed a hybrid peptide of Bld-1-kla.…”
Section: Bld-1mentioning
confidence: 99%